THE INFLUENCE OF HEAT TREATMENT ON MICROSTRUCTURE AND MECHANICAL STRENGTH OF LATERITIC NICKEL STEEL - Satrio Herbirowo; Bintang Adjiantoro (Widyariset, 2016)
Indonesia has abundant resources of lateritic nickel ore and coal. However, this resource has not been considered as a main raw material in the Indonesian steel industry. Therefore, this study are aimed to investigate several aspects of lateritic nickel intrinsic propertiesand its potency through heat treatment process. Nickel laterite steels are usually used for bridge and building construction steel. Their properties can be improved in various ways, such as by conducting temper heat treatment. This research reported the influences of heat treatment on microstructure and mechanical strength in nickel laterite steel. Samples were austenitized at 900ºC and subsquently tempered at 100 ºC, 200 ºC, 300 ºC, 400 ºC, 500 ºC, and 600ºC. Metallographic observation was conducted by using an optical microscope meanwhile mechanical strength were conducted by tensile test and surface hardness. The results showed evolution of mictrostructure in nickel laterite steel after heat treatment. The microstructure formed consisted of martensite temper. The presence of inclusion can affect brittle behavior of the lateritic nickel. The optimum tempering temperature was 200 ºC. The result of Scanning Electron Microscope (SEM) fractography showed the dimple and intergranular fracture has caused a more ductile and mechanical behavior which is compatible with construction steels standard.